Pusa Navrang grape: A Naga woman’s SuccessfulStory of Production and Value-Addition - Pongener, Alemwati; Singh, Sanjay (Indian Horticulture, 2024)
Sub-tropical viticulture in the North Eastern India has picked up in the last few decades with the collective efforts of some enthusiastic and amateur growers. At present, Bangalore Blue cultivar is the major variety grown in Mizoram and adjoining states. Almost a decade back, Ms Sentiben, a tribal woman from Nagaland, out of curiosity planted a few rooted cuttings of a unique teinturier variety ‘Pusa Navrang’ at Dimapur from the ICAR-Indian Agricultural Research Institute, New Delhi. The coloured bunches inspired her to learn and perfect the art of making quality red wine. Later she made this her entrepreneurial venture and labelled her produce as LURO wine, which is today a total sellout in the town. With this taste of success, she is now venturing into it as a professional entrepreneur and plans to establish a nursery for area expansion with her women group of 10 members who are helping in pooling the produce for bulk production of Pusa Navrang. She and her group are planning big to produce certified ‘Organic red wine’.